Mediated Non-geminate Recombination in Ternary Organic Solar Cells Through a Liquid Crystal Guest Donor - Yin, Ao; Zhang, Dongyang; Wang, Jianqiu; Zhou, Huiqiong; Fu, Zhiqiang; Zhang, Yuan (Frontiers in Chemistry, 2020)
The approach via ternary blends prompts the increase of absorbed photon density and resultant photocurrent enhancement in organic solar cells (OSCs). In contrast to actively reported high efficiency ternary OSCs, little is known about charge recombination properties and carrier loss mechanisms in these emerging devices. Here, through introducing a small molecule donor BTR as a guest component to the PCE-10:PC71BM binary system, we show that photocarrier losses via recombination are mitigated with respect the binary OSCs, owing to a reduced bimolecular recombination. The gain of the fill factor in ternary devices are reconciled by the change in equilibrium between charge exaction and recombination in the presence of BTR toward the former process. With these modifications, the power conversion efficiency in ternary solar cells receives a boost from 8.8 (PCE-10:PC71BM) to 10.88%. We further found that the voltage losses in the ternary cell are slightly suppressed, related to the rising charge transfer-state energy. These benefits brought by the third guest donor are important for attaining improvements on key photophysical processes governing the photovoltaic efficiencies in organic ternary solar cells.